Unconventional Care: Offspring Abandonment and Filial Cannibalism Can Function as Forms of Parental Care - Davenport, Mackenzie E.; Bonsall, Michael B.; Klug, Hope (Frontiers in Ecology and Evolution, 2019)
Parental care is a key life-history trait that increases offspring fitness. When one thinks of parental care, nurturing behaviors such as guarding, provisioning, and grooming typically come to mind. However, such conventional forms of care often co-occur with offspring abandonment or filial cannibalism (the consumption of one’s offspring). Offspring abandonment and filial cannibalism are typically viewed as evolutionary conundrums that are contradictory to parental care. Here, we hypothesize that when offspring survival is density dependent, offspring abandonment and filial cannibalism can themselves function as forms of parental care for remaining offspring. We use a mathematical model to test this hypothesis. Our results suggest that offspring abandonment and filial cannibalism can function as forms of parental care. These results have the potential to broaden our general understanding of what is considered to be parental care.